Hubble Space Telescope observations of [O iii] emission in nearby QSO2s: physical properties of the ionized outflows. Issue 1 (20th October 2020) - Trindade Falcão, Anna; Kraemer, S B; Fischer, T C; Crenshaw, D M; Revalski, M; Schmitt, H R; Vestergaard, M; Elvis, M; Gaskell, C M; Hamann, F; Ho, L C; Hutchings, J; et al.
ABSTRACT: We use Hubble Space Telescope /Space Telescope Imaging Spectrograph long-slit G430M and G750M spectra to analyse the extended [O iii ] λ5007 emission in a sample of 12 nearby ( z < 0.12) luminous ( L bol > 1.6 × 10 45 erg s −1 ) QSO2s. The purpose of the study is to determine the properties of the mass outflows of ionized gas and their role in active galactic nucleus feedback. We measure fluxes and velocities as functions of radial distances. Using cloudy models and ionizing luminosities derived from [O iii ] λ5007, we are able to estimate the densities for the emission-line gas. From these results, we derive masses of [O iii ]-emitting gas, mass outflow rates, kinetic energies, kinetic luminosities, momenta, and momentum flow rates as a function of radial distance for each of the targets. For the sample, masses are several times $10^{3}$ –$10^{7}\, {\rm M_{\odot }}$ and peak outflow rates are from 9.3 × 10 −3 to $10.3\, {\rm M_{\odot }}\, {\rm yr^{-1}}$ . The peak kinetic luminosities are (3.4 × 10 −8 )–(4.9 × 10 −4 ) of the bolometric luminosity, which does not approach the (5.0 × 10 −3 )–(5.0 × 10 −2 ) range required by some models for efficient feedback. For Mrk 34, which has the largest kinetic luminosity of our sample, in order to produce efficient feedback there would have to be 10 times more [O iii ]-emitting gas than that we detected at its position of maximum kinetic luminosity. Three targets show extended [O iii ] emission, but compact outflow regions. This may be due to different mass profiles or different evolutionary histories.